Creutzfeldt-Jakob Disease (CJD) in Southeast Asia: a diagnostic challenge - Abdul Rashid, Anna Misya'il; Md Noh, Mohamad Syafeeq Faeez; Hoo, Fan Kee; Wan Sulaiman, Wan Aliaa; Inche Mat, Liyana Najwa; Basri, Hamidon (Pakistan Medical Association, 2017)
Creutzfeldt-Jakob disease (CJD) is a rare disorder that presents with a myriad of symptoms. Early features may include pyramidal and cerebellar signs with very vague history of dementia. This makes diagnosis particularly challenging; especially when a different diagnosis is more common. Unavailability of laboratory testing in most centers also limits the diagnosis. Newer literature agrees on the reliability of neuroimaging, namely magnetic resonance imaging (MRI) and its role in providing a clear diagnosis in CJD. We report a patient presenting with dementia, pyramidal symptoms and later had myoclonic jerks. He refused lumbar puncture, and electroencephalogram (EEG) changes were not typical of CJD. Only on MRI were we able to prove his diagnosis as workup for alternative diagnoses were negative. Though there is no curative intervention, supportive treatment proves of utmost importance during the course of illness.